2021
DOI: 10.3389/fnbeh.2021.710725
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Acute and Chronic Stress on CA1 Spatial Coding and Gamma Oscillations

Abstract: Chronic and acute stress differentially affect behavior as well as the structural integrity of the hippocampus, a key brain region involved in cognition and memory. However, it remains unclear if and how the facilitatory effects of acute stress on hippocampal information coding are disrupted as the stress becomes chronic. To examine this, we compared the impact of acute and chronic stress on neural activity in the CA1 subregion of male mice subjected to a chronic immobilization stress (CIS) paradigm. We observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 85 publications
(133 reference statements)
1
8
0
Order By: Relevance
“…2g ). This finding is in line with previous work showing that chronic stress in adulthood decreases gamma oscillation power within the hippocampus 62 . Given that high-frequency oscillations in vHIP inhibit the basolateral amygdala and reduce freezing in a contextual fear conditioning paradigm 63 , the reduction of vHIP gamma oscillation power in MSEW diestrus mice might coincide with diminished emotional regulation.…”
Section: Resultssupporting
confidence: 93%
“…2g ). This finding is in line with previous work showing that chronic stress in adulthood decreases gamma oscillation power within the hippocampus 62 . Given that high-frequency oscillations in vHIP inhibit the basolateral amygdala and reduce freezing in a contextual fear conditioning paradigm 63 , the reduction of vHIP gamma oscillation power in MSEW diestrus mice might coincide with diminished emotional regulation.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, activity within the CA1 region has been shown to be differentially attuned to acute versus chronic stressors. In a longitudinal study where local field potentials were recorded within the CA1 region on the first and last day of chronic stress, researchers found that the initial stress experience increased firing in the CA1, while repeated exposure to stress led to decreased firing (Tomar et al 2021). Without the temporal resolution, we do not have clarity on the specific activation pattern of the CA1, however, it is clearly highly involved in the initial acute stress response of future Resilient mice.…”
Section: Discussionmentioning
confidence: 99%
“…LFPs are integrative excitatory and inhibitory synaptic processes [139] that span a wide range of frequencies, including theta (4-10 Hz), beta , and gamma (30-120 Hz) oscillations, as well as sharp-wave ripples (SWRs, 110-200 Hz) [140]. Rodent studies found that restraint+tailshock and CRS enhanced hippocampal theta rhythms [114] and SWRs [141] and decreased CA1 slow/fast gamma power [142]. Chronic unpredictable stress (restraint+noise+shaking+cold air stream) also heightened theta power in ventral hippocampus (vHPC) and basolateral amygdala (BLA) and increased vHPC-BLA coherence [143], whereas chronically restrained rats (2-hr/day for 10 days) exhibited decreased beta and gamma synchrony between CA1-CA3 areas but increased lateral amygdala (LA)-hippocampus synchrony with strong LA→CA1 directional activity [144].…”
Section: Neural Activitymentioning
confidence: 99%